Exploiting fluorescent zinc(ii) and copper(ii) complexes for enantiomeric excess determination of hydroxycarboxylates. Issue 63 (8th July 2020) - Sheykhi, Sara; Mosca, Lorenzo; Pushina, Mariia; Dey, Kaustav; Anzenbacher, Pavel
Abstract : Fluorescent Zn(ii ) complexes with quinolino-1, 2-diaminocylohexane ligands recognize enantiomeric excess in scalemic mixtures of α-hydroxycarboxylates. Abstract : Chiral hydroxycarboxylates are useful compounds in the syntheses of natural products, pharmaceutical intermediates, and drugs. Here, we report on Zn- and Cu-containing sensors that can distinguish between enantiomers of hydroxycarboxylates through the quenching or the enhancement of fluorescence. A Zn-based sensor—[Zn RR L] 2+ —is used in an assay to perform analyses of enantiomeric excess (% ee) of scalemic mixtures of α-hydroxycarboxylates and various drugs including the statin drug atorvastatin. This assay enables determination of mixtures of enantiomers across the range from 0 to 100% ee.